ANALISIS STRUKTUR RETORIKA PROBLEM JUSTIFYING PROJECT PADA TEKS PENDAHULUAN ARTIKEL JURNAL BIDANG PENELITIAN TINDAKAN KELAS - Sasih Karnita Arafatun (Edutainment, 2019)
The goal of this study is to find out rhetoric structure in introduction text journal articles research class action with ideal according structure model of PJP rethoric. This research is using a descriptive method. The data of this study is the author's speech in part of introduce journal artcle "BISA" and "Bahasa dan Seni" journal articles in the field of classroom action research. Based on the results of the analysis has found the same steps in each of the dominant stages of writing AJP "BISA" and "Bahasa dan Seni" are stages 1 with step 1C explaining a brief history of the field of research and 1E making general claims; step 2 with step 2A introducing the research topic, 2B identifies the research problem, 2C reviews the relevant literature; stage 3 with the 3D step states that it is interested in examining the problem; and step 4 with step 4A explains the purpose of the study, 4B states the research question, and 4G proposes a solution to the research problem. In case of journal "Language and Art" there are steps at each dominant stage, stages 1: 1A define important terms, 1B refers to government policies; stage 3: 3C states that the topic is important to study; and stage 4: 4C describes the specific characteristics of the study, 4D states the benefits of the study, 4E announces the research findings, 4F states the research hypothesis.